Reforming Maine's Education Funding Process - Dow, Patrick; Townsend, Ralph (Maine Policy Review, 1998)
In recent years funding for Maine K-12 education has been a source of almost constant dissension. As authors Patrick Dow and Ralph Townsend note, much of this dissension began in the early 1990s with the legislature's decision to reduce funding for local education. Shrinking community budgets for local education have led to political battles over who gets what and have led to changes in the school funding formula established in the 1970s. The authors argue that these changes have eroded the principles of equity on which the 1970s formula was built. They trace the history of education funding in Maine, explain the mechanics of the current funding formula, and assess the impacts of recent changes to the formula. They conclude with a set of recommendations that call for, in part, setting a realistic local operating cost mill rate; the removal of income and cost of living from the formula; and modifications to the circuit breaker and homestead-exemption programs.
Keywords: Maine school funding